Single and multi optical soliton light trapping and switching using microring resonator - Amiri, Iraj S. (2013)
We propose a system of microring resonator (MRR) incorporating with an add/drop filter system under nonlinearity condition where trapping of single and multi optical soliton can be simulated and used to many applications in optical switching and signal processing. Nonlinear Kerr effect type of the light inside the MRR induces the chaotic behavior within the device. By using appropriate soliton input power and MRR parameters, continuous spatial and temporal signals are generated spreading over the spectrum. In this work, narrow single and multi pulse of solitons can be trapped within the proposed system. There are two forms of localized soliton pulses as spatial and temporal in which required security can be performed via ultra-short pulses of soliton where the high capacity can be obtained using multiple trapping techniques. Results obtained show that single temporal and spatial soliton pulse of 4.8 picosecond (ps), 17.5 picometer (pm), 712 femtosecond (fs), 0.34 nanometer (nm) and 84 fs could be trapped where multi soliton pulses with FSR of 1.45 nm, 3.6 nanosecond (ns) and FWHM of 40 pm, 140 ps are localized within the add/drop filter system.